1962
DOI: 10.1071/bi9620700
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Relationships Between Central Primary Skin Follicles During their Development in Sheep

Abstract: SwmmaryThe spatial patterns of central primary follicles have been measured during development and compared on six body positions and hetween Romney X South. down cross and Merino shepp. The patterns are similar in both breeds on aU the body positions investigated and appear to be constant between 70 and 140 days of foetal age.The actual measurement of spatial relationships shows that the distribution of central primary follicles is highly uniform, and gives support to the idea that these follicles 'may compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1963
1963
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The spatial relationships between central primary follicles during their initiation and development ,vere reported in an earlier paper (Claxton 1962). The results shO\ved that the pattern of central primaries was similar in six body regions of both Romney X Southdown cross and Merino sheep, and that it was invariant during initiation and subsequent foetal development.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…The spatial relationships between central primary follicles during their initiation and development ,vere reported in an earlier paper (Claxton 1962). The results shO\ved that the pattern of central primaries was similar in six body regions of both Romney X Southdown cross and Merino sheep, and that it was invariant during initiation and subsequent foetal development.…”
Section: Introductionsupporting
confidence: 57%
“…Schinckel (1955), Stephenson (1959), and Schinckel and Short (19GI) have concluded that heavier foetuses have a greater total number of primary follicles. The distribution of central primary follicles is highly uniform yet there is no evidence that the pattern has a directional component (Claxton 1962). These considerations suggest that the mechanism controlling the distribution of central primary follicles may be a competitive one whereby new follicles appear at sites most distant from existing follicles.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations